Peningkatan Pengetahuan Mengenai Penyakit Kardiovaskular dan Manfaat Konsumsi Sayur dan Buah Pada Masyarakat Desa Pasir Angin, Cileungsi, Jawa Barat - Wiyati, Tuti; Nurhasna, Nurhasna; Hikmawantia, Ni Putu Ermi (Society : Jurnal Pengabdian Masyarakat, 2023)
Cardiovascular disease is still at the top cause of death in Indonesia and globally. Cardiovascular diseases include hypertension, stroke, and heart disease. Knowledge is still ignored and also an unhealthy lifestyle caused increasing worse risk of its. The aim was to educate about the knowledge of cardiovascular disease and the importance of consuming vegetables and fruits as preventive and treatment of its in community of Pasir Angin Village, Cileungsi, West Java. The implementation method started with education through explanation of cardiovascular disease followed by providing information on the content of active compounds in vegetables and fruits that is beneficial for its. The succeeded of this activity was analized by the average pre-test and post-test and feed back that actually seemed by some reacted of pasticipants on discussed session. From the results has known that the knowledge of participants before being given education was 65%, increasing to 81%. Conclusion: cardiovascular disease education is still very much needed in communities widely.